Survival Time and Prognostic Factors in Patients with Spinal Metastases: A retrospective cohort and prognostic study - Piyapromdee, MD, Urawit; Adulyanukosol, MD, Varinthorn (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To determine the survival time in patients with spinal metastases and identify the factors associated with survival time. Methods: A retrospective cohort study of patients with spinal metastases treated at Maharat Nakhon Ratchasima Hospital between January 2009 and December 2013 was performed. The following assessment parameters were recorded: General demographic data, ambulatory status, the number of involved vertebrae, visceral organ metastases, lung metastases or lung tumor, known or unknown primary sites of metastases, surgical operation, radiotherapy and the survival period. The Kaplan-Meier survival analysis, the log-rank test and Cox proportional hazard regression model were used to determine the survival analysis. Results: There were 119 patients included in the study; 62 were female. The mean age was 61 years old. The most common identified sites of primary tumor were lung, prostate, cervix, breast and multiple myeloma, but 47.9% were from unknown primary sites. The median survival time was 132 days. The multivariate survival analysis revealed statistically significant factors were: type of primary malignancy, evidence of lung metastases or lung cancer. Conclusion: The prevalence of an unidentifiable primary site is high and the most common site is the lungs followed by the prostate. The presence of lung metastases or lung tumor were the factors that associated with poor patient survival.